Water-Energy-Food nexus symposium 2023 Agenda - Ringler, Claudia (CGIAR, 2023)
The OECD predicts there will be 9 billion people on Earth by 2050. At the same time, it is anticipated that global water needs will rise by 55%, energy consumption by 80%, and food production by 60%, all of which could have an impact on land use patterns. In light of these forecasts, the importance of the Water Energy Food (WEF) nexus thinking is needed more than ever. In this symposium, we aim to provide a comprehensive overview of the state-of-the-art, gaps and advances in WEF nexus research. We invited well-known keynotes and prominent early-career scientists to cover a wide range of topics including water and carbon footprints, the role of forests and food waste, governance, and many more. Sounds interesting? Then see you in November!